2014
DOI: 10.1038/bonekey.2013.213
|View full text |Cite
|
Sign up to set email alerts
|

History of the discovery of vitamin D and its active metabolites

Abstract: Before the twentieth century, it was not possible to describe the essentials of a diet that could support life, growth and reproduction of higher animals. The discovery of vitamin A by McCollum and Davis in 1913 ushered in the era of accessory food substances culminating in the achievement of that goal. It included the discovery of vitamin D and its production in skin caused by ultraviolet light. This was followed by a description of its actions at the physiological level that resulted in a healthy skeleton an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
148
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(152 citation statements)
references
References 94 publications
0
148
0
4
Order By: Relevance
“…Together with other transcription factors such as retinoid X receptor (RXR), the complex of vitamin D, VDR and RXR is formed and bound to vitamin D response elements of multiple genes, regulating directly and/or indirectly their expression (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…Together with other transcription factors such as retinoid X receptor (RXR), the complex of vitamin D, VDR and RXR is formed and bound to vitamin D response elements of multiple genes, regulating directly and/or indirectly their expression (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D was initially identified as being useful for the treatment of rickets. A lack of vitamin D can lead to the onset of rickets in younger animals and chondropathy in adult animals (15). The present study showed that different concentrations of 1α,25-(OH) 2 D 3 may inhibit the formation and activity of OCs, as well as downregulating the expression levels of CA II, CK and MMP-9.…”
Section: Discussionmentioning
confidence: 64%
“…Vitamin D was first discovered by McCollum and Davis in 1913 and in 1932 Askew et al isolated vitamin D 2 from an irradiation mixture of ergosterol and later vitamin D 3 was identified by Windaus and Bock in 1937, which was formed in the skin as a result of UV irradiation of 7-dehydrocholesterol and later on in 1978, actual isolation and identification of vitamin D 3 was proved by Esvelt et al by mass spectrometry. 3 Very few foods naturally contain vitamin D, and foods that are fortified with vitamin D are often inadequate to satisfy either a child's or an adult's vitamin D requirement. Sources of vitamin D is mainly from synthesis of vitamin D (specifically cholecalciferol or vitamin D 3 ) in the skin.…”
Section: Introductionmentioning
confidence: 99%